Synthesis of oleophilic electron-rich phenylhydrazines - Jankowiak, Aleksandra; Kaszyński, Piotr (Beilstein Journal of Organic Chemistry, 2012)
Phenylhydrazines 1 substituted with two or three long-chain alkyl, alkoxy or alkylsulfanyl groups were successfully prepared by acid-induced removal of the Boc group in hydrazides 2. The reaction is carried out with 5 equivalents of TfOH in CF3CH2OH/CH2Cl2 at −40 °C for 1.5 min. Under these conditions, the deprotected hydrazine 1 is fully protonated, which increases its stability in the reaction medium. The hydrazines were isolated in 60–86% yields and purities >90%. The hydrazides 2 were obtained in 43–71% yields from aryl bromides 5, which were lithiated with t-BuLi and subsequently reacted with di-tert-butyl azodicarboxylate (DTBAD).
Keywords: arylhydrazines; methodology; synthesis